Membangun Jiwa Wirausaha Mahasiswa Berbasis Potensi Lokal: Integrasi Kearifan Lokal dalam Pendidikan Kewirausahaan - Nur Chotimah; Abdul Kholiq (Journal of Innovative and Creativity, 2025)
This study aims to explore how the integration of local wisdom into entrepreneurship education can shape students' entrepreneurial character that is innovative, contextual, and rooted in local culture. Using a descriptive qualitative approach and a case study at Universitas Muhammadiyah Maumere, the research involved students from the economics education program who participated in project-based entrepreneurship courses. Data were collected through interviews, observations, and documentation. The findings reveal that integrating local wisdom significantly enhances students’ understanding of regional potential, encourages the creation of culturally inspired products, and builds confidence and entrepreneurial motivation. The Project-Based Learning (PjBL) approach proved effective in linking entrepreneurship material to the students’ socio-cultural realities. Students not only developed economically valuable business ideas but also perceived entrepreneurship as a means of cultural preservation and local community empowerment. These findings suggest that local wisdom-based entrepreneurship education holds strong potential as a contextual learning model that can be adapted to support sustainable economic development.